Analysis of Dairy Value Chains in Organized Sectors of Haryana: A Chain Wide Learning Approach - Soumya Mohapatra; Sendhil R., Akshith Sai Pabba (Indian Journal of Extension Education, 2022)
Despite the fact that India is the highest milk producer in the world, dynamic production and consumption pattern of milk furnishes immense scope for analyzing the existing dairy value chains in the country. Value chain analysis is important to understand the prevailing market situation, interrelationships among the core actors, their market participation and issues & challenges involved in the value chain. Main objective of the study is to analyze the value chains of milk in organized dairy sector comprising of co-operative and private dairies of Haryana. Chain wide learning method was employed to analyze the detailed value chain of milk considering the stakeholders from input suppliers to consumers for improving the performance of value chain. The empirical evidences indicated that procurement, chilling and processing costs were higher in the co-operative dairy than the private dairy plant. However, the co-operative plant realized higher producers’ share in consumers’ price (76.16%) than the private dairy plant (75.15%) with a higher degree of marketing efficiency (3.20). Therefore, attention must be given the mobilize large number of farmers towards organized dairy sector by providing modern technologies and training facilities to strengthen the value chain management practices for tapping the commercial potential of Indian dairy sector.